(untitled) (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY To evaluate the efficacy of high-pressure balloon dilatation (HPBD) as treatment of primary obstructive megaureter (POM) in paediatric patients, we analysed the data of our institute from June 2018 to September 2019. METHODS 14 patients, aged 5 months to 5 years, with POM were treated with HPBD. All patients had a distal ureter dilatation greater than 7 mm associated with obstructive features on a mercaptoacetyl triglycine-3 diuretic renogram scan, and a voiding cystourethrogram without vesicoureteral reflux. HPBD was performed in 12 patients, whereas 2 patients (14%), aged 5 and 6 months, required open surgical treatment because of failure to pass the balloon catheter through the vesicoureteral junction. The procedure was performed with a 5 Fr balloon catheter for two cycles of 5 minutes each at 17 atm. A double-J stent and a urinary catheter were inserted at the end of procedure in all patients. RESULTS No operative complications or symptoms or recurrence were recorded in our series. The patients were generally discharged 24 hours after surgery. All the patients showed an improvement on ultrasonography at the postoperative follow-up, with no evidence of obstruction. During the procedure a clear stenotic ring was identified in 10 of the 12 patients, which disappeared in all 10 cases after the HPBD technique. CONCLUSIONS Based on our experience, HPBD may be considered the first-line surgical approach in the treatment of POM in children, avoiding bladder surgery in most cases.